2017
DOI: 10.26493/1854-4231.12.333-353
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Norms, Trust, and Fairness on Voluntary Tax Compliance in Austria

Abstract: Existing literature stresses the importance of economic factors when aiming to increase voluntary tax compliance. However, emerging voices also point out to relevant social factors, but emphasize that more research needs to be carried out for their verification. Therefore, in this article, research was conducted to provide further evidence to show how social factors have an influence on voluntary tax compliance. The research is the first attempt to replicate the results of the structural model of Jimenez and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The follow-up studies use the psychological approach in analyzing tax compliance, such as tax morale (Jones, 1991; Andreoni et al , 1998; Dolores et al , 2010; Cyan et al , 2016), taxpayers’ trust (Hammar et al , 2009; Dijke and Verboon, 2010; Kostritsa and Sittler, 2017; Faizal et al , 2017), social norms (Damayanti, 2012; Bobek et al , 2013) and the feeling of caring and worrying (Bayissa and Van-Dijke, 2017). Several studies also combine the economic approach with the psychological approach in investigating the tax compliance phenomenon (Kirchler et al , 2008; Kastlunger et al , 2013; Kogler et al , 2013; Palil et al , 2017) or as commonly known as the slippery slope framework.…”
Section: Introductionmentioning
confidence: 99%
“…The follow-up studies use the psychological approach in analyzing tax compliance, such as tax morale (Jones, 1991; Andreoni et al , 1998; Dolores et al , 2010; Cyan et al , 2016), taxpayers’ trust (Hammar et al , 2009; Dijke and Verboon, 2010; Kostritsa and Sittler, 2017; Faizal et al , 2017), social norms (Damayanti, 2012; Bobek et al , 2013) and the feeling of caring and worrying (Bayissa and Van-Dijke, 2017). Several studies also combine the economic approach with the psychological approach in investigating the tax compliance phenomenon (Kirchler et al , 2008; Kastlunger et al , 2013; Kogler et al , 2013; Palil et al , 2017) or as commonly known as the slippery slope framework.…”
Section: Introductionmentioning
confidence: 99%
“…Research in the area of voluntary tax compliance has observed that perceived fairness of the tax system is an important determinant of voluntary tax compliance (Damayanti et al, 2015; Kogler et al, 2013). According to Kostritsa and Sittler (2017), a positive response to tax compliance depends on how individuals perceive the fairness of the authorities. Casal et al (2016) have also observed that a high sense of fairness experienced by individuals in how authorities treat them is correlated with higher trust for that authority and higher willingness to comply with the guidelines and regulations established by the authority.…”
Section: Literature Review and Hypothesis Formulationmentioning
confidence: 99%
“…Based on the slippery slope theory, the extent to which individuals or businesses are willing to voluntarily obey the tax laws and faithfully file their tax returns depends on their perception of the tax authorities in terms of fairness, trust, and knowledge of the tax system. One of the important factors that have been identified as an important determinant of voluntary tax compliance is the perceived fairness of the tax system (Kostritsa & Sittler, 2017). This claim is supported by Thomas (2012), who posits that the perception of taxpayers regarding the fairness and efficiency of the tax system is an important determinant of voluntary tax compliance.…”
Section: Literature Review and Hypothesis Formulationmentioning
confidence: 99%